#Metoo Movement Trending in Research Work: A Scientometric Analysis, 2018-2023 - Roy, Pradip; Maity, Bapan Kumar (Journal of Data Science, Informetrics, and Citation Studies)
The #MeToo movement creates history in social media, it became the third most influential social media campaign of 2017. This article presents #MeToo research trends in an analysis of publication productivity, authorship, geography and we use PlumX metric to observed trends in highly cited publications in virtual media. It has been found that over the past six years, #MeToo research has produced 1,725 publications and received 9,744 citations. The most works (348) were published in 2020, while the most cited works (2900) were in 2019. The highest number of articles will be published during the COVID-19 period (2020-2022). Publication results over the past six years tend to change logistically over time. The United States of America (USA) reported the highest number of #MeToo inquiries during this period. In the United States of America, 817 publications with 4795 citations were recruited. In the Asian subcontinent, India had a maximum of 67 publications and 296 citations, although India's activity rate was below average. According to PlumX Metrics, the top 10 most cited publications are readers and some of these publications are trending on social media platforms. So, we conclude that #MeToo movement in social media trending topic now become a serious research topic in the last six years.
Keywords: #MeToo; Scientometrics; Bibliometrics; Logistic Curve; Average Citation per Paper; Degree of Collaboration; Proportional Counting; Activity Index; PlumX.